1983
DOI: 10.1136/thx.38.6.463
|View full text |Cite
|
Sign up to set email alerts
|

Impaired tracheobronchial clearance in patients with mild stable asthma.

Abstract: ABSTRACr Tracheobronchial mucociliary clearance was measured with the radioaerosol technique in 25 patients with stable, mild asthma, none of whom was taking systemic corticosteroids. The results were compared with those obtained from a control group of 25 healthy subjects matched for age and sex. All patients and healthy subjects were non-smokers. Ventilatory function was significantly impaired in the asthmatic group, which resulted in a more central initial tracheobronchial deposition of inhaled radioaerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…In our study, we have also demonstrated reduced lung mucociliary clearance in mild asthmatics compared to normal subjects, as reported previously [9,10]. The reduction in asthmatics is an underestimate of the time effect, because the radioaerosol was deposited on average more proximally within the lungs of asthmatics compared to normal volunteers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we have also demonstrated reduced lung mucociliary clearance in mild asthmatics compared to normal subjects, as reported previously [9,10]. The reduction in asthmatics is an underestimate of the time effect, because the radioaerosol was deposited on average more proximally within the lungs of asthmatics compared to normal volunteers.…”
Section: Discussionsupporting
confidence: 90%
“…Lung mucociliary clearance may be affected by a number of physiological, pharmacological, environmental and pathological factors [8]. In patients with mild stable asthma and those who are in clinical remission, lung mucociliary clearance is depressed, and the mechanisms by which this occurs are unclear [9,10].…”
mentioning
confidence: 99%
“…Tracheobron chial mucociliary clearance is impaired in stable asthma (2) and worsens during acute exacerbations (3). The principal cause of death from asthma is asphyxiation from intraluminal airway obstruction by widespread mucus plugs (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical asthma manifestations include recurrent episodes of at least partially reversible wheezing, dyspnoea, cough, and increased airway mucus production. The asthmatic airway is characterized by epithelial damage, mucus hypersecretion, submucosal glandular hypertrophy, and goblet cell hyperplasia finally impairing mucociliary clearance (3)(4)(5)(6)(7). While efficient mucociliary clearance plays a fundamental role in the innate immune response system of the conducting airways, the impaired mucociliary clearance in asthma leads to prolonged exposure of inhaled pollutants and aeroallergens to the respiratory epithelium and an increased susceptibility to infections (4).…”
mentioning
confidence: 99%